Transdermal electrophysiological recordings of diet-induced small fiber peripheral neuropathy using a needle electrode array in mice and man - Blaszkiewicz, Magdalena; Caron, Lydia; Villinski, Brooke; Passarelli, Joshua; Towne, Julia M.; Story, Naeemah M.; Merchant, Erin; Khan, Furrukh S.; Emanetoglu, Nuri; Kass, Leonard; Smith, Rosemary L.; Townsend, Kristy L. (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundDiabetic peripheral neuropathy (DPN) is a common complication of diabetes. Proactive treatment options remain limited, which is exacerbated by a lack of sensitive and convenient diagnostics, especially early in disease progression or specifically to assess small fiber neuropathy (SFN), the loss of distal small diameter axons that innervate tissues and organs.MethodsWe designed, fabricated, tested, and validated a first-of-its-kind medical diagnostic device for the functional assessment of transdermal small fiber nerve activity. This device, the Detecting Early Neuropathy (DEN), is an electrically conductive needle array designed to record nerve electrical activity in the skin and subdermal tissues, as a feature of a broader theragnostic platform.ResultsDEN recordings were validated across a time course of diet-induced PN in mice, using statistical and computational analyses and compared to other SFN measures. Based on these preclinical mouse data, the device design was adapted to obtain recordings in human with a flexible printed circuit board to mold to the leg or other skin regions. The DEN successfully recorded various types of neural activity in mouse and human, with or without stimulation, including validated action potentials and electromyography signals.ConclusionNew functional diagnostic tools like DEN offer a promising outlook for patients needing an earlier or more sensitive diagnosis of DPN/SFN, to allow for earlier and more effective treatment options, especially as more become available in the clinic in future years.